Environmental and genetic effects on growth traits in Jamunapari kids - SINGH, M K; RAI, B; SINGH, N P (The Indian Journal of Animal Sciences, 2011)
Jamunapari kids (2759) born during 1985 to 2007 at the Central Institute for Research on Goats, Makhdoom, Mathura, Uttar Pradesh, India were used to estimate the body weight and average daily weight gain (ADG). The overall least squares means for body weight at birth, 3, 6, 9 and 12 months of age were 3.14±0.02, 10.52±0.07, 14.95±0.10, 20.57±0.13 and 25.68±0.15 kg, respectively. The least square mean for ADG during 0–3, 3–6 and 6–12 growth periods were 82.05±0.74, 49.18±0.76 and 59.59±0.61g/day, respectively. The period and season of birth, type of birth, sex, feeding management system and weight of dam at kidding has significantly affected the growth traits at all the ages. Kids born in autumn were of lowest birth weight (3.03±0.05), however, higher growth rate of autumn born kids during 0–3 and 3– 6 months of age significantly excel their body weight over the kids born in other seasons from the age of 3 month onwards. Males were born with higher body weight and maintained their superiority of weight and weight gain over females. Kids born from prima-parous and aged does has slightly less weight at birth and 3 months of age. Kids reared under intensive feeding showed higher (